Portfolio investment response to U.S. monetary policy announcements: An event study analysis using high frequency data from Mexico - Marco Aurelio Hernández Vega (Banco de México, 2017)
We study how unconventional monetary policy announcements affect the entry of foreign investment in debt and equity in Mexico, placing special focus on announcements related to the third QE program and the taper tantrum episode. A novel dataset on daily debt and equity flows, that maps Balance of Payments data quite well, allows this paper to provide a better insight into movements of capital. The results suggest that both equity and debt flows appear to react immediately to unexpected U.S. monetary policy announcements, in particular if these are considered as bad news by investors. In turn, results using weekly data support the idea that investors interested in fixed income instruments move more prudently than those interested in equity who react quickly.
Keywords: E4; E52; F21; F3; F62; G10; 330; Monetary Policy Announcements; Unconventional Monetary Policies; Foreign Portfolio Investment; Mexican Equity and Bond Market